Ideological Domination: Deconstructing the Paradox of the American Dream and the Working Class Promise - Stoneman, Betty (Stance: an international undergraduate philosophy journal, 2014)
The “American Dream” and “Working Class Promise” ideologies are ubiquitously dispersed in American society. These ideologies posit values of equality and opportunity. In this paper, I deconstruct these two ideologies in order to examine the effects these ideologies have on income inequality, social inequality, and social immobility. I argue these ideologies create a paradox in society whereby the more these ideologies are believed, the more the ideologies exacerbate income inequality, social inequality, and social immobility.